L’économie sociale et solidaire dans les politiques d’inclusion en Argentine (2003-2017) - Arnaud Trenta (Sociologies, 2022)
Since the 2000s, inclusion projects through self-managed work have been structured in various Latin American societies thanks to the convergence of social movements and social policies around the category of social and solidarity economy. Based on the case of Argentina, the article analyses, on the one hand, the socio-economic and political transformations that make the emergence of this model of socio-productive development possible and, on the other hand, the ambivalence of the policies supporting the social and solidarity economy, which oscillate between employment policies and assistance policies. The analysis is based on fieldworks conducted between 2007 and 2018 in different scales (federal, provincial, municipal, neighbourhood), mainly in the provinces of Buenos Aires and Mendoza.